2010
DOI: 10.1115/1.4001321
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a High Temperature Polymer Electrolyte Membrane Fabrication Process

Abstract: Cost, durability, and reliability are the major issues hindering the commercialization of polymer electrolyte membrane fuel cells. Electrolyte membranes present in the fuel cell fails under chemical, thermal, and mechanical influences, which, in turn, results in the overall fuel cell failure. In the present work, 2D studies are performed to understand the effect of manufacturing processing conditions and materials on the quality of the high-temperature membranes. Multiphase computational fluid dynamics models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
2
6
0
1
Order By: Relevance
“…This decrease in the critical web velocities for the onset of a coating defect with increasing viscosity suggests that the fluid viscosity has a negative impact on the size of the operating window. This behavior is consistent with the literature observations for the case of homogenous Newtonian solutions …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This decrease in the critical web velocities for the onset of a coating defect with increasing viscosity suggests that the fluid viscosity has a negative impact on the size of the operating window. This behavior is consistent with the literature observations for the case of homogenous Newtonian solutions …”
Section: Resultssupporting
confidence: 93%
“…Previous studies on dilute particle dispersions have reported that, when the coating defect is air entrainment, the addition of particles to a coating fluid improves the coating window . However, in the case of fumed silica nanoparticle dispersions in PPG the coating defect is ribbing, where the ribbing instability is known to occur due to large adverse pressure gradient, a different mechanism compared to air entrainment, which is commonly associated with a failure of dynamic wetting contact line . Lin et al have examined the influence of particle addition when the coating defect was ribbing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 67 ] In addition, some coating defects such as ribbing, dripping, rivulets, and air entrainment will occur during the coating process. [ 70,71 ] Despite this, slot‐die coating is still a versatile process which is widely used for fabricating thin and uniform films, such as in polymer electrolyte membrane fuel cells, [ 72,73 ] solar cells, [ 74,75 ] lithium‐ion batteries, [ 76,77 ] and flexible organic electronics. [ 78,79 ] In recent years, slot‐die coating is also successfully applied in fabricating large‐area perovskite films, the following text will summarize the recent advances in highly efficient PSCs using slot‐die coating method.…”
Section: The Advances Of Various Large‐scale Fabrication Methodsmentioning
confidence: 99%
“…Existing studies on the issue of modeling penetration are almost related with these three coating methods. Among these three coating methods, slot die coating has attracted increased attention in recent years for manufacturing of membrane fuel cells, solar cells, lithium‐ion batteries, and flexible organic electronics . This is because slot die coating is a premetered process by which the thickness of the coated layer can be controlled precisely.…”
Section: Modeling Domainmentioning
confidence: 99%